IMPACT OF BOARD CHARACTERISTICS, OWNERSHIP STRUCTURE AND RETURN ON ASSETS OF LISTED HEALTCARE FIRMS IN NIGERIA - Ahmed, Abubakar Zik-Rullahi; Bamidele, Durojay John (Journal Of Islamic Finance And Accounting Research, 2015)
This study examined the impact of board characteristics, ownership structure return on assets of listed healthcare firms. This study used annual reports and accounts of listed healthcare firms in Nigeria as sources of data. The data collected was analysed using descriptive statistics, a correlation matrix and multiple regression analysis. The findings show that ownership structure has a positive significant impact on ROA of listed healthcare, Board compensation has no significant impact on the ROA of listed healthcare firms in Nigeria, Board diligence, Independent Audit Committee and Board diversity have negative significant effect on ROA of listed healthcare firms in Nigeria and Independent Directors have positive insignificant impact on the ROA of listed healthcare firms in Nigeria. It is however recommended that Healthcare firms should encourage concentrated ownership or institutional investors who can provide strategic oversight and improve financial performance. Firms should align executive remuneration with performance-based incentives to enhance motivation and strategic decision-making rather than increasing meeting frequency, firms should focus on improving meeting quality, ensuring discussions are strategic and result-oriented.